To Assess the Use of Mobile Phone and Depression among the Selected Pre-UniversityCollege Going Students - Mujawar, Suhel Ismail; Potdar, Nutan J.; Mohite, Vaishali R.; Patil, Sangita; Pawar, Ajit Anandrao; Choudhari, Samir K. (International Journal of Psychosocial Rehabilitation, 2020)
The use of cellular phone has increased rapidly in the recent years and this overuse of mobile phones makes the person dependent and addicted. The dependence syndrome in which users of mobile phone show some problematic behaviors which leads to nervousness and melancholy if they arenot allowed to use a mobile phone. Therefore, to reduce depression among the college going students it is necessary to assess the mobile phones use.Study assessed the cellphone use and depression among the selected pre-university college going students.A cross sectional design was usedto conduct the study among the pre-university college going students at karad.A survey of 110 pre-University College going students, selected by non-probability purposive sampling method.Permission was taken from the setting;data collection was done by using addiction scale for use ofsmart phone – short version the questions were directed towards assessment of addiction for Smart phone and PHQ-9depression questionnaire used for assessing the depression among Pre-University College Going Students.Result of the present study shows that the correlation coefficient (r) value was 0.5235 the despair andsmartphone dependencyhad been positively correlated with two tailed p value < 0.0001 which was considered as significant. Per day time spent on cell phone, purpose of cell tele phone use and duration of mobile phone use had been substantially associated with smartphone addiction at p < 0.0001, p < 0.0001 and p < 0.0496 respectively. Also, the depression was significantly associated with time spent on cell phone per day, purpose of use of cellular phone and residency at p < 0.0028, p < 0.0001 and p < 0.0202 respectively.Depression may be associated with overuse of mobile phone. Such overuse may lead to depression. Necessary steps must be taken to prevent this kind of addiction among pre-university college going students and other people also.